Viewpoint: Climate impacts on agriculture: Searching for keys under the streetlight. (August 2020) - Hertel, Thomas W.; de Lima, Cicero Z.
Highlights: The majority of climate impact studies focus on changes in yields for a four staple crops. There has been little research into climate change and farm labor productivity. Research into climate impacts on knowledge capital is needed. Climate change impacts on people in the tropics outweigh that on crops. Ignoring labor impacts understates losses in the world's poorest countries. Abstract: This paper provides a critical assessment of the literature estimating the consequences of climate impacts in agriculture and the food system. This literature focuses overwhelmingly on the impact of elevated CO2 concentrations in the atmosphere, higher temperatures and changing precipitation on staple crop yields. While critically important for food security, we argue that researchers have gravitated to measuring impacts 'under the streetlight' where data and models are plentiful. We argue that prior work has largely neglected the vast majority of potential economic impacts of climate change on agriculture. A broader view must extend the impacts analysis to inputs beyond land, including the consequences of climate change for labor productivity, as well as for purchased intermediate inputs. Largely overlooked is the impact of climate change on the rate of total factor productivity growth and the potential for more rapid depreciation of the underlying knowledge capital underpinning this key driver of agricultural output growth. This broader view must also focus more attention on non-staple crops, which, while less important from a caloric point of view, are critically important in redressing current micronutrient deficiencies in many diets around the world. The paper closes with numerical simulations that demonstrate the extent to which limited input and output coverage of climate impacts can lead to considerable underestimation of the consequences for food security and economic welfare. Of particular significance is the finding that humans in the humid tropics are likely more vulnerable to heat stress than are many of the well-adapted crops, such as rice. By omitting the impact of heat stress on humans, most studies of climate impacts greatly understate the welfare losses in the world's poorest economies.